The Influence of Influencer Perception and Product Knowledge on Purchase Decisions at Mie Gacoan Pekanbaru - Wahyudi, Hasbi; Yulianti, Alma; Herwanto, Jhon (Yayasan Mata Pena Madani, 2024)
Purchase decisions are activities undertaken by individuals directly involved in making decisions to buy a product. Several factors influence an individual's decision to purchase a product, including perception, product knowledge, and motivation. This study aims to examine the role of influencer perception and product knowledge on purchase decisions, mediated by consumer motivation, at Mie Gacoan Pekanbaru Panam. The study involved 249 respondents, who were customers of Mie Gacoan Pekanbaru Panam. Data collection utilized four scales: influencer perception, product knowledge, consumer motivation, and purchase decision. The collected data were analyzed using a quantitative approach based on Structural Equation Modeling (SEM) to test the hypotheses and proposed model. The analysis results showed that the proposed model—demonstrating the influence of influencer perception and product knowledge on purchase decisions mediated by consumer motivation—fit the empirical data. Influencer perception, product knowledge, and consumer motivation significantly influenced purchase decisions. Furthermore, consumer motivation was proven to be a mediating variable between influencer perception and purchase decisions.